Visual recognition memory differentiates dementia with Lewy bodies and Parkinson's disease dementia. Issue 7 (7th February 2007) - Mondon, K; Gochard, A; Marqué, A; Armand, A; Beauchamp, D; Prunier, C; Jacobi, D; de Toffol, B; Autret, A; Camus, V; Hommet, C
Abstract : Objective: To compare cognitive impairments in dementia with Lewy bodies (DLB) and Parkinson's disease dementia (PDD), to discriminate between the two entities. Methods: 10 DLB and 12 PDD consecutive patients performed a neuropsychological battery designed to assess several cognitive domains: verbal and visual memory (Delayed Matching to Sample (DMS)-48), language, gnosia, praxia and executive functions. Results: DLB patients had poorer performances in orientation (p<0.05), Trail Making Test A (p<0.05) and reading of names of colours in the Stroop Test (p<0.05). Their scores were also lower in the visual object recognition memory test (DMS-48), in both immediate (p<0.05) and delayed recognition (p<0.05). No differences were observed in the other tests. Conclusion: Despite global similarities in cognitive performances between DLB and PDD patients, we observed important differences: in particular, DMS-48, a test of visual object recognition memory and visual storage capacity, was poorer in DLB patients.